Ultrastructural lung pathology following brain injury combined with femur shaft fracture in a rat model. Issue 3 (March 2015) - Chen, Xiaobin; Song, Yaozong; Liu, Zhi; Zhang, Jianzheng; Sun, Tiansheng
Abstract : BACKGROUND: This study aimed to explore the early pathologic changes in the lung ultrastructure in rat models of isolated or multiple traumatic injuries. METHODS: Ninety-six rats were divided into a control group, a unilateral femur fracture group, a brain injury group, and a unilateral femur fracture combined with brain injury group. At 1, 6, 12, and 24 hours following model creation, the rat lungs were isolated and examined under a transmission electron microscope. A lung injury scoring model was used to evaluate the ultrastructural changes in the organelles of Type II alveolar epithelial cells (AEC-II). The ultrastructural changes and lung injury scores were compared among the four groups. RESULTS: Mild ultrastructural damage was seen in the single-trauma groups. In the unilateral femur fracture group, the organelle morphology alleviated within 24 hours. The brain injury group showed more obvious ultrastructural changes, and some organelles were irreversibly damaged. This ultrastructural damage to the AEC-II was significantly augmented in the combined injury group; in this group, the damage was most obvious, occurred the earliest, involved the widest area, continued to progress throughout the study, and apparently worsened in 24 hours. The lung injury scores increased at all the time points in the three experimental groups compared with the control group and were significantly higher in the combined injury group than in the other groups. CONCLUSION: Ultrastructural AEC-II damage was significantly augmented in the combined injury model compared with the single-injury models. The pulmonary condition should be considered when treating this type of injury.